Strategies for Optimizing Acute Burn Wound Therapy: A Comprehensive Review - Andrei Cretu; Andreea Grosu-Bularda; Eliza-Maria Bordeanu-Diaconescu; Florin-Vlad Hodea; Vladut-Alin Ratoiu; Catalina-Stefania Dumitru; Mihaela-Cristina Andrei; Tiberiu-Paul Neagu; Ioan Lascar; Cristian-Sorin Hariga (Medicina)
Recent advancements in acute burn wound therapy are transforming the management of burn injuries, with a focus on improving healing times, graft integration, and minimizing complications. However, current clinical treatments face significant challenges, including the difficulty of accurately assessing wound depth and tissue viability, which can lead to suboptimal treatment planning. Traditional closure methods often struggle with issues such as delayed wound closure, limited graft survival, inadequate tissue regeneration, and insufficient vascularization. Furthermore, managing infection and minimizing scarring remain persistent obstacles, impacting functional recovery and aesthetic outcomes. Key areas of innovation include advanced imaging techniques that enable more precise assessment of wound depth, size, and tissue viability, allowing for more accurate treatment planning. In addition, new closure strategies are being developed to accelerate wound closure, enhance graft survival, and address challenges such as tissue regeneration, vascularization, and infection prevention. These strategies aim to optimize both functional recovery and aesthetic outcomes, reducing scarring and improving the quality of life for burn patients. While promising, these emerging techniques require further research and clinical validation to refine their effectiveness and expand their accessibility. Together, these innovations represent a significant shift in acute burn care, offering the potential for more personalized, efficient, and effective treatments.